Dying autologous cells as instructors of the immune system. (26th November 2014) - Munoz, L E; Herrmann, M; Berens, C
Summary: In an organism, cell death occurs at many different sites and in many different forms. It is frequently part of normal development or serves to maintain cell homeostasis. In other cases, cell death not only occurs due to injury, disease or infection, but also as a consequence of various therapeutic interventions. However, in all of these scenarios, the immune system has to react to the dying and dead cells and decide whether to mount an immune response, to remain quiet or to initiate healing and repopulation. This is essential for the organism, testified by many diseases that are associated with malfunctioning in the cell death process, the corpse removal, or the ensuing immune responsiveness. Therefore, dying cells generally have to be considered as instructors of the immune system. How this happens and which signals and pathways contribute to modulate or shape the immune response is still elusive in many conditions. The articles presented in this Special Issue address such open questions. They highlight that the context in which cell death occurs will not only influence the cell death process itself, but also affect the surrounding cellular milieu, how the generation and presence of 'eat me' signals can have an impact on cell clearance, and that the exact nature of the residual 'debris' and how it is processed are fundamental to determining the immunological consequences. Hopefully, these articles initiate new approaches and new experiments to complete our understanding of how cell death and the immune system interact with each other.